Photoionization of the 4d subshell of barium - (:unkn) unknown (My University, 1990)
The photoionization cross section and angular distribution asymmetry parameter of the 4d 10 subshell of atomic barium have been calculated using many-body perturbation theory and the relativistic random-phase approximation modified to include relaxation effects. Our main purpose is to determine whether relaxation and polarization effects can account for the large difference between recent 4d photoemission experiments and total absorption experiments. Polarization effects have been included by evaluating many-body diagrams. Results are compared with experiments and other calculations. © 1990 IOP Publishing Ltd.